2013
DOI: 10.4187/respcare.02068
|View full text |Cite
|
Sign up to set email alerts
|

Individualized PEEP Setting in Subjects With ARDS: A Randomized Controlled Pilot Study

Abstract: BACKGROUND: Low-tidal-volume ventilation may be associated with repetitive opening and closing of terminal airways. The use of PEEP is intended to keep the alveoli open. No method of adjusting the optimal PEEP has shown to be superior or to improve clinical outcomes. We conducted a pilot study to evaluate the effect of setting an individualized level of PEEP at the highest compliance on oxygenation, multiple-organ-dysfunction, and survival in subjects with ARDS. METHODS: Subjects with ARDS ventilated with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 42 publications
(57 reference statements)
1
78
0
Order By: Relevance
“…Pintado et al 39 recently reported a randomized controlled study to evaluate the effect of setting an individualized PEEP at the highest C RS . Subjects in the C RS -guided group had a nonsignificant improvement in 28-d mortality (21% vs 39%, P ϭ .12), perhaps because the study was underpowered.…”
Section: Respiratory Mechanics During Mechanical Ventilationmentioning
confidence: 99%
“…Pintado et al 39 recently reported a randomized controlled study to evaluate the effect of setting an individualized PEEP at the highest C RS . Subjects in the C RS -guided group had a nonsignificant improvement in 28-d mortality (21% vs 39%, P ϭ .12), perhaps because the study was underpowered.…”
Section: Respiratory Mechanics During Mechanical Ventilationmentioning
confidence: 99%
“…Respiratory mechanics monitoring of critically ill patients receiving mechanical ventilation can be used to guide treatment and monitor changes in patient condition [1], [2]. The underlying respiratory mechanics of a patient, indicative of the lung condition, can be masked by any level of patient breathing effort [3].…”
Section: Introductionmentioning
confidence: 99%
“…31 In comparison to patients receiving PEEP according to the ARDS Network F IO 2 /PEEP table, Pintado et al found significantly fewer days of multi-organ system dysfunction and hemodynamic failure, as well as more ventilator-free days. There was a trend toward decreased mortality.…”
Section: See the Original Study On Page 1416mentioning
confidence: 99%